Detection of Syphilis by Serologic Tests in Pregnant Iranian Women, Shiraz, Iran: - Taghinia, Mohammad Amin; Motamedifar, Mohammad; Hassanzadeh, Parvin; Hassanzadeh, Yashgin (Galen Medical Journal, 2013)
Background: Syphilis is an infectious disease caused by Treponema pallidum and transmitted via sexual contact, infected discharge and blood as well as vertical transmission. It causes various impacts on women during pregnancy and their newborns which results in various complications. Thus, screening of syphilis is routinely performed during pregnancy. Choosing to perform a specific screening test is based on the prevalence of the disease in the target population which needs adequate information in this regard. The aim of the present study was to determine the prevalence of syphilis among pregnant women in Shiraz, South-west of Iran. Methods: in this 15 month prospective study, 1100 pregnant women aged between 15 â€“ 42 years, referred to University affiliated hospital in shiraz, Iran were included Â Blood samples were obtained from all of our study population for performing RPR test. FTA-ABS serologic test was carried out on positive cases of RPR test. Results: 15 suspicious cases with weakly positive RPR test were detected but in all of them FTA-ABS tests were negative. Conclusions: The prevalence and incidence of syphilis was low in our area which may be due to variable reasons, such as reduction in the rate of unsafe and unprotected sex, improving knowledge, and adequate health care services. More studies are still needed to decide whether syphilis screening is beneficial in our area and should be considered as a routine test in pregnancy.